4CPS-049 Ceftobiprole in empirical treatment of bone and joint infections: survey of the prescriptions, respect of the protocol and economic evaluation over 6 months. (March 2019) - Debailleul, M; Di Paolo, J; Genay, S; Dezeque, H; Senneville, E; Putman, S; Migaud, H; Loiez, C; Decaudin, B; Odou, P
Abstract : Background: In our hospital, a protocol is used in empirical treatment for bone and joint prosthetic device infections. It combines the use of efficient antibiotics on methicillin resistant staphylococci (MRS) with the search for gene mec A indicating resistance to methicillin (answer is obtained within 2 hours after the sampling). Since January 2018, the combination of daptomycin and cefepime as empirical antibiotic therapy has been replaced by ceftobiprole. Antibiotics are administered until the result of resistance genes is available. In the case of negative response, a relay by cefepime is performed until adaptation to antibiogram results. Purpose: The aim of this study was to evaluate the respect of this protocol and the economic impact of using ceftobiprole instead of the daptomycin-cefepime combination. Material and methods: A prospective monocentric study was performed between January and July 2018. Data, collected by the analysis of all prescriptions, were: indications, previous history of MRS, prescriptions (monotherapy, way of administration and posology), results of expression of mec A, number of administrations and relays. Ceftobiprole-related cost was compared to theoretical cost of the daptomycin-cefepime combination. Results: A total of 154 patients received ceftobiprole after surgery because of bone and/or prosthetic infections: (83/154 (55%) osteoarticular prosthesis; 59 (38%) osteosynthesis; 10 (6.5%) induced membrane technique; and one (0.5%) external fixator. Five (3%) patients had a previous history of MRS infection. Ceftobiprole monotherapy was given to 152 patients and cefepime combination in two. All prescriptions respected dosage and administration way. Eight (5%) of the prescriptions did not comply with the protocol, including indications (six; 4%) and monotherapy (two; 1%). Mec A search was negative for 139 (90%) of patients, positive for nine (6%) and uninterpretable for six (4%). Patients received 2.34±2.57 ceftobiprole injections (2.02±1.80 if mec A search was negative). When negative, a switch to cefepime was performed for 130 (94%) patients. The cost gain from this antibiotic therapy switch was €24 501 in 6 months. Conclusion: This study showed a respect of ceftobiprole use in this protocol. Most of the prescriptions were compliant with protocol (indications, administrations). If mec A search was negative, the relay was appropriate mainly by cefepime. The economic gain was demonstrated over this period, but it will be reassessed with the arrival of the generic of daptomycin. References and/or acknowledgements: No conflict of interest.